Development and evaluation of automation system for irrigation scheduling in broccoli (Brassica oleracea) - KUMAR, JITENDRA; PATEL, NEELAM; SINGH, RAMADHAR; SAHOO, PRAMOD KUMAR; SUDHISHRI, SUSAMA; SEHGAL, VINAY KUMAR; MARWAHA, SUDEEP; SINGH, AWANI KUMAR (The Indian Journal of Agricultural Sciences, 2021)
The present study was attempted to develop an automated irrigation system for real-time irrigation management using soil moisture sensor, decision support system, level sensor, level controller, GSM receiver, transmitter, solenoid valve, water meter and pump. The performance of developed automated irrigation system was evaluated under different methods of irrigation in broccoli crop. The field experiment in Broccoli crop was conducted (2013-14 and 2014-15 ) in split plot design with three irrigation methods, i.e. check-basin, furrow and drip irrigation as main plot treatments, and irrigation control methods, i.e. automated and manually-controlled assub-plot treatments. Water saving, water productivity and cost economics of developed system were calculated and compared under different studied irrigation methods. It was found in the present study that the sensor based automated drip irrigation system resulted in highest irrigation water productivity (9.7 kg/m3) and crop water productivity (10.6 kg/m3) as compared to all other treatments. Similarly, the highest benefit-cost ratio (3.24) and water saving was obtained under the sensor based automated drip irrigation system. Therefore, the developed indigenous sensor based automated drip irrigation system can be used for efficient irrigation management in the broccoli crop.